2006
DOI: 10.1002/ca.20282
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the medial sesamoid bone associated with metatarsophalangeal pain

Abstract: Pain at the first metatarsophalangeal (MTP) joint can result from inflammation, chondromalacia, flexor hallucis brevis tendinitis, osteochondritis dessecans, fracture of a sesamoid bone, avascular necrosis of sesamoids, inflamed bursae, intractable keratoses, infection, sesamoiditis, gout arthropathy, and rheumatoid arthritis. Congenital absence of a sesamoid bone is extremely rare. We present a 17-year-old male patient with pain at the plantar aspect of the right MTP joint associated with congenital absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Most of the patients are adolescents or young adults, and women are more affected than men 2 , 8 . Although both of the sesamoids may be affected, the tibial sesamoid is subjected to greater loads and is therefore more susceptible to this condition 1 , 3 , 5 , 10 . Another cause of this condition could be the natural pronation of the first metatarsal, which places the tibial sesamoid in a more prominent position (2) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the patients are adolescents or young adults, and women are more affected than men 2 , 8 . Although both of the sesamoids may be affected, the tibial sesamoid is subjected to greater loads and is therefore more susceptible to this condition 1 , 3 , 5 , 10 . Another cause of this condition could be the natural pronation of the first metatarsal, which places the tibial sesamoid in a more prominent position (2) .…”
Section: Discussionmentioning
confidence: 99%
“…They absorb pressure, reduce attrition and protect and stabilize the metatarsophalangeal joint and the tendons of the long flexors of the hallux. They act as a fulcrum for increasing the mechanical resistance of the tendons at the time of the impulse of gait and provide a dynamic function to the hallux, through raising the head of the first metatarsal and distributing the weight-bearing in the lateral projection of the forefoot 3 , 4 , 5 . Despite the crucial role played by the sesamoid bones in the mechanics of the forefoot, complaints resulting from pathological conditions in these structures are often neglected or poorly diagnosed and managed.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients are adolescents or young adults, and BONE SCINTIGrAPHy E C O A r NUCLEAR MEDICINE Apr 12, 2010 women are more affected than men (2,8) . Although both of the sesamoids may be affected, the tibial sesamoid is subjected to greater loads and is therefore more susceptible to this condition (1,3,5,10) . Another cause of this condition could be the natural pronation of the first metatarsal, which places the tibial sesamoid in a more prominent position (2) .…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnoses include nonspecific sesamoiditis; osteomyelitis; trauma with fractures; pseudarthrosis; bursitis; sympathetic-reflex dystrophy syndrome; gout and other diseases with deposition of crystals, such as hyperuricemia; joint inflammation diseases such as rheumatoid arthritis, psoriatic arthritis and reactive arthritis; and abnormal alignment, dislocation and osteoarthritis of the sesamoid bone (1,2,5,8,10) . The main symptom is mechanical pain that starts gradually and is reflected in the plantar surface of the head of the first metatarsal, on palpation, on putting weight on the hallux and in the final phase of the gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…On a review of the literature, Le Minor found that in 3305 feet there were no reports of sesamoid absence. 4 There are eleven case reports of single sesamoid agenesis in the literature, seven cases of which are tibial sesamoid agenesis [5][6][7][8][9][10] and three cases of fibular sesamoid agenesis. There is one reported case of unilateral complete agenesis of the sesamoids 14 and one bilateral complete agenesis of the sesamoids reported in the literature.…”
mentioning
confidence: 99%